Purple Economy, the Economic Vision for Culture in the Kingdom of Saudi Arabia: A Study in Political Geography - Lawind, Vian Ahmed Mohammed (Al-Adab Journal, 2022)
The Purple Economy is one of economy types that is considered as a basic pillar of the economic development of all countries .It is named as the economy integrated with culture and purple colour is the symbol of creativity which it is named on .It appeared for the first time in France and from it the importance in this type of economy has began in all countries and reached to Sauidia Arabia as it is a country of oil and growing economy that attempts to be opened and expand to all economic development and growing .It was observed that the cultural sector contributes in 3% of Gross Domestic Product as well as Saudi Arabia has 16 cultural branches directed by 11 offices that facilitate these branches work.